Next Steps for Cyber Norms in ASEAN - Ang, Benjamin (2018)
ASEAN has appointed Singapore to propose a mechanism to enhance ASEAN cyber coordination, and has also agreed in principle to certain voluntary norms of behaviour in cyberspace. This choice of norms gives clarity to the region’s direction, especially while international discussions have stalled.